Kepuasan Pasien Rawat Inap Ditinjau dari Kualitas Pelayanan, Harga dan Fasilitas di Lumajang - Sukma Irdiana (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
The purpose of this study was to determine the effect of service quality, price and facilities on the satisfaction of class III inpatients, both partially and simultaneously. This research was conducted at Wijaya Kusuma Lumajang Hospital. The research method used in this study is Multiple Linear Regression. The results of this study indicate that partially the variable quality of service has a significant effect on the satisfaction of class III inpatients at Lumajang Wijaya Kusuma Hospital. Whereas for the price variable and facility variable there is no significant effect on the satisfaction of class III inpatients at Lumajang Wijaya Kusuma Hospital. From the results simultaneously, the variables of service quality, price and facilities have no significant effect simultaneously on the satisfaction of class III inpatients at Wijaya Kusuma Lumajang Hospital with a coefficient of determination (adjusted R2) obtained at 0.167. This means that 16.7% of patient satisfaction can be explained by independent variables, namely service quality, price and facilities, while the remaining 83.3% patient satisfaction is influenced by other variables not examined in this study. The limitations of this study are only examining the effect of variable service quality, price and facilities on patient satisfaction, while other variables that influence patient satisfaction are expected to be investigated by future researchers.